Molting while breeding? Lessons from New World Tyrannus Flycatchers - Jahn, Alex E. [UNESP]; Bejarano, Vanesa [UNESP]; Guzman, Marcela Benavides [UNESP]; Brown, Leone M.; Provinciato, Ivan C. Carvalho [UNESP]; Cereghetti, Joaquin; Cueto, Victor R.; Giraldo, Jose I.; Gomez-Bahamon, Valentina; Husak, Michael S.; LePage, Heather K.; MacPherson, Maggie; et al. (Springer, 2017)
Songbirds must annually undergo two energetically demanding but important activities: breeding and feather molt. Due to the high energetic investment that each demands, these two events are generally not carried out simultaneously. However, substantial variation in the level of annual reproductive investment among populations may result in variation in molt-breeding overlap between them. With the goal of understanding whether different songbird populations overlap molt and breeding, and, if so, to determine directions for research on the potential tradeoffs involved, we describe the relationship between clutch size, molt, and energetic condition within a genus of New World Flycatchers (Tyrannus). Of 219 Flycatchers sampled, only one individual molted flight feathers while breeding, suggesting that molting flight feathers and breeding simultaneously is too energetically expensive at any clutch size. However, some Flycatchers molted body feathers during the breeding season. When we tested for an effect of clutch size, sex and energetic condition on body molt intensity during the breeding season, only clutch size and sex had significant effects, with a negative effect of clutch size on body molt intensity in males but not in females. Based on these results, we develop a set of hypotheses to guide future studies on the potential tradeoffs between investment in reproduction and molt.
Keywords: Clutch size; Feather molt; Reproduction; Temperate; Tropical; Tyrannidae